Implementasi Manajemen Strategi Dalam Peningkatan Mutu Pendidikan di SMAN 10 Tasikmalaya - Yonandi, Yonandi (LPPM Universitas Bina Bangsa, 2022)
Based on the observation results, several problems were found that can interfere with school activities, including teachers attending training, but the results obtained from the training are still not enough, have limited facilities and infrastructure, lack of understanding of teachers about the use of IT, besides that there is still a lack of awareness from teachers of their responsibilities as educators, do not understand how to manage administration in schools, inadequate school facilities and infrastructure, information from outside the school that is late to school, lack of coordination between teachers and stakeholders. The objectives of this study are 1) To find out how schools formulate/formulate strategies. 2) To know how to implement school strategies. 3) To find out the school evaluates the management strategies that have been implemented. 4) To determine the quality of education achieved by schools by implementing strategic management. 5) To know what strengths, weaknesses, opportunities and threats are faced by the school. 6) To find out the strategic steps taken by the school in overcoming the threat of weaknesses, opportunities and what threats are faced by the school. Therefore, this research uses qualitative methods, this is related to the focus of the problems discussed, namely the application of strategic management in realizing school excellence at SMAN 10 Tasikmalaya. Data collection techniques in this study used interview and observation techniques. Based on the results of research that the way the school formulates / formulates a strategy has been implemented by SMAN 10 Tasikmalaya, how to implement the school strategy has been carried out at SMAN 10 Tasikmalaya, the school has evaluated the management strategy that has been implemented, the advantages achieved by the school by implementing strategic management are already owned. What strengths, weaknesses, opportunities and threats are faced by the school has been analyzed and the strategic steps taken by the school in overcoming the threats of weaknesses, opportunities and threats faced by the school have been implemented